Incidence of Different Clinical & Histopathological Types of Ameloblastoma in Southern Punjab - Noor Ul Ain, Uzma Tariq, Muhammad Asad, Tahmasub Faraz Tayyab, Samar Nazir, Syeda Rabia Rahat Geelani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Second-most common odontogenic tumor is ameloblastoma. This is because to its high tumor recurrence rate, poor treatment options, clinical features, and prevalence. Objective: To examine the occurrence rates and offer clinical and pathological insights into the different histological types of ameloblastoma in Southern Punjab. Method: This retrospective study was conducted at CIMS Dental College Multan within a duration of 16 months from Dec 2022 to March 2024. Clinico-pathological data for biopsy-proven 31 cases of ameloblastoma reported from different areas of Southern Punjab were analyzed anthropologically and descriptively over 16 months. Descriptional statistical analyses were performed on the data that was obtained using the statistical software programme known as SPSS version 20.0. The threshold for determining the level of significance was established at p<0.05. Results: Ameloblastoma was more common in southern Punjab in the fourth to fifth decade, peaking in the fifth with a wider age range of 16–63 years. All described patients had unicystic or multicystic mandible involvement and complained of progressively increasing, painless lower jaw enlargement. Fourteen patients had unicystic while 17 were having multicytic appearance. Radiographically, 17 cases had multilocular radiolucency (54.84%), and 14 unilocular radiolucencies (45.16%) were reported. Histopathologically, the Follicular ameloblastoma (61.3%) was the most prevalent pattern, followed by plexiform type (16.13%), Acanthomatous (9.68%), desmoplastic (9.68%) and Granular Cell type (3.3%). Conclusion: This study describes clinical/radiological and histopathological types of ameloblastoma in Southern Punjab. This study provides pathologists and clinicians with Clinico-Pathological insights into all documented cases since these variations have different biological characteristics. Keywords: Ameloblastoma, Clinico-Pathological, Mandible, Follicular, Odontogenic